Landmark papers in neurology - Turner, Martin R.; Kiernan, Matthew C. (Landmark papers in ... series., 2015)
Current understanding of neurological disease has been evolving over the past 150 years. With the increasing and earlier sub-specialization of neurology trainees, and their variable exposure to higher academic study, there is little opportunity to put this development into a historical context as a whole. Understanding the 'evidence-base', or appreciating the lack of it in some cases, is an important part of training but this is rarely presented in a palatable, entertaining form. Part of the Landmark Papers in series, this book brings together the ten most important papers for each sub-speciality has developed.